2011
DOI: 10.19030/jber.v9i4.4208
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Of Birth Order On Financial Risk Tolerance

Abstract: This study examines birth order as a predictor of financial risk tolerance. Three hundred sixty-eight individuals, drawn predominantly from a large university in the Southwestern United States, completed a psychometrically sound financial risk tolerance measure (Grable and Lytton, 1999). The results confirmed previous literature in regard to gender and education as predictors of risk tolerance. However, for the first time, firstborn individuals were shown to be significantly less risk tolerant than later-born … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…This instrument has been widely used (see for example, Grable, 2000;Grable and Lytton, 2003;Chatzoglou, 2010;Gilliam and Chatterjee, 2011). The instrument itself consists of 20 multiple-choice questions.…”
Section: Methodsmentioning
confidence: 99%
“…This instrument has been widely used (see for example, Grable, 2000;Grable and Lytton, 2003;Chatzoglou, 2010;Gilliam and Chatterjee, 2011). The instrument itself consists of 20 multiple-choice questions.…”
Section: Methodsmentioning
confidence: 99%
“…A growing body of research, however, has also suggested that birth order influences an individual's risk-taking propensity, an important and stable aspect of personality outside of the Big Five 2 (Frey, Pedroni, Mata, Rieskamp, & Hertwig, 2017;Nicholson, Soane, Fenton-O'Creevy, & Willman, 2005) that indicates an individual's tendency to engage in risk across contexts. For example, birth order has been shown to be positively associated with risky behaviors, such as risky adolescent behaviors (Argys et al, 2006), participation in risky sports (Nisbett, 1968), and risky financial decisions (Gilliam & Chatterjee, 2011). Meta-analytic evidence, albeit in the sports context, has suggested that birth order's relationship with risk-taking propensity may even be stronger than its relationship with other personality aspects, such as the Big Five (Sulloway & Zweigenhaft, 2010) CEO BIRTH ORDER AND STRATEGIC RISK TAKING…”
Section: Birth Order and Sibling Rivalrymentioning
confidence: 99%
“…Scholars have also examined the relationship between birth order and risk taking in the business context. Gilliam and Chatterjee (2011), for example, surveyed students and found that later-borns were more willing to make risky investments. Morgan (2009) examined financial investments decisions, and found that later-borns tend to take greater financial risks and are more willing to gamble for a higher payoff.…”
Section: Birth Order and Sibling Rivalrymentioning
confidence: 99%
See 1 more Smart Citation
“…1, p. 433): Later-borns select more dangerous sports than firstborns, and, when they choose the same sport, they take more risks when playing that sport. In the same vein, one small-scale self-report study of financial risk tolerance (n = 368) found that firstborns have a lower risk tolerance than later-borns, and are less likely to allocate a majority of their assets to stocks (14). Another small-scale study (n = 200), however, found no effect of birth order on self-reported risk behaviors [e.g., birth control, unprotected sex (15)].…”
Section: The Empirical Evidencementioning
confidence: 99%